PREPARATION AND CHARACTERIZATION OF SODIUM CARBOXYMETHYL CELLULOSE FROM KAPOK (CEIBA PENTANDRA) ALPHA-CELLULOSE - ARDIYANITA, PUTRI ZAHRA; SUTRIYO, SUTRIYO; SURYADI, HERMAN (International Journal of Applied Pharmaceutics, 2020)
Objective: This study aimed to obtain sodium carboxymethyl cellulose (NaCMC) from α-cellulose of the hulls of kapok (Ceiba pentandra) and determining its identity and characteristics base on compendial requirements and compared to the reference (standard). Methods: α-Cellulose was isolated from kapok hulls and used to generate NaCMC powder through alkalization and carboxymethylation. Alkalization was performed using 25% NaOH (containing sodium tetraborate), whereas carboxymethylation was using sodium monochloroacetate. Identification and characterization were performed through infrared spectrum analysis using Fourier transform infrared, qualitative analysis, organoleptic examination, morphologic examination, and topographical analysis using scanning electron microscopy (SEM), and X-ray diffraction. Tests conducted were pH determination, sulfated ash content, moisture content, loss on drying, particle density, and viscosity. Results: The obtained NaCMC powder was yellowish-white with a similar infrared spectrum as the NaCMC standard. The powder had a degree of substitution of 0.57 and a pH of 8.5. According to SEM, the obtained powder had a similar morphology as the NaCMC standard, although the synthesized NaCMC had a rougher surface. The obtained NaCMC also had a similar diffractogram as the NaCMC standard, which was characterized by the presence of crystalline and amorphous structures. Besides, the NaCMC powder had a similar moisture content (8.50%), sulfated ash content (36.43%), and loss on drying (9.87%) as the standard, whereas its 1% viscosity value (20.6 cP) was substantially different. Conclusion: NaCMC generated from α-cellulose of kapok hulls fulfills compendial requirements and has similar characteristics to reference.